ANALISIS PENGENDALIAN KUALITAS PRODUK DI CV. BILO DATANG - Aloysius Pansewidi; Ronald P C Fanggidae; Reyner F Makatita (Universitas Nusa Cendana, 2020)
The purpose of this study is to analyze the level and the type of damage in the production process CV.Bilo Datang and the solutions of quality control are carried out. The method used in this research is quantitative descriptive analysis method using Pareto diagram analysis tools and Cause-effect diagrams. The results of the study showed that the quality control conducted by the company was less than optimal, especially in controlling for half defective products. This is due to several things such as lack of employee skills and maintenance of machinery and equipment that is less than the maximum resulting in the product being half defective. Although in the amount of damage is greater than half defective products but there are also products damaged due to pest attack on wood. The solution provided by the researcher is also appropriate to the stage of the damage that occurred. Keywords: Product Quality Control, Level of damage and Type of damage